Transposons, environmental changes, and heritable induced phenotypic variability - Piacentini, Lucia; Fanti, Laura; Specchia, Valeria; Bozzetti, Maria Pia; Berloco, Maria; Palumbo, Gino; Pimpinelli, Sergio (Chromosoma, 2014)
The mechanisms of biological evolution have always been, and still are, the subject of intense debate and modeling. One of the main problems is how the genetic variability is produced and maintained in order to make the organisms adaptable to environmental changes and therefore capable of evolving. In recent years, it has been reported that, in flies and plants, mutations in Hsp90 gene are capable to induce, with a low frequency, many different developmental abnormalities depending on the genetic backgrounds. This has suggested that the reduction of Hsp90 amount makes different development pathways more sensitive to hidden genetic variability. This suggestion revitalized a classical debate around the original Waddington hypothesis of canalization and genetic assimilation making Hsp90 the prototype of morphological capacitor. Other data have also suggested a different mechanism that revitalizes another classic debate about the response of genome to physiological and environmental stress put forward by Barbara McClintock. That data demonstrated that Hsp90 is involved in repression of transposon activity by playing a significant role in piwi-interacting RNA (piRNAs)-dependent RNA interference (RNAi) silencing. The important implication is that the fixed phenotypic abnormalities observed in Hsp90 mutants are probably related to de novo induced mutations by transposon activation. In this case, Hsp90 could be considered as a mutator. In the present theoretical paper, we discuss several possible implications about environmental stress, transposon, and evolution offering also a support to the concept of evolvability.